Use and coverage of middle land coverage of the Itapecuru river basin (Research, Society and Development, 2022)
The watershed is a unit of analysis and planning. The study aimed to carry out a survey of land use and land cover in the middle course of the Itapecuru river basin, MA. For the elaboration of the map of use and coverage of the medium course, the database available from the MapBiomas platform was used. To generate the map, the ArcGis software was used. Field activities were carried out to recognize the main types of use and coverage, obtain aerial images and check mapping information, using a Remotely Piloted Aircraft (RPA). The middle course of the Itapecuru river basin has different types of land use and cover, the natural vegetation is composed of forest formation (9,822.68 km2), savanna formation (10,217.57 km2) and grassland formation (329.18 km2). The following types of uses were detected: planted forest (17.99 km2), pastures (5,255.95 km2), sugarcane cultivation (0.01 km2), soybean cultivation (51.86 km2), crops storms (101.21 km2) and urbanization (67.05 km2). The study on land use and land cover makes it possible to verify the conditions of the basin, in addition to generating information to support public policies.